2018
DOI: 10.1002/anie.201811946
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐High‐Molecular‐Weight Polymers Produced by the Immortal Phosphine‐Based Catalyst System

Abstract: A strong organophosphorus superbase, N‐(diphenylphosphanyl)‐1,3‐diisopropyl‐4,5‐dimethyl‐1,3‐dihydro‐2H‐imidazol‐2‐imine (IAP3) was combined with a sterically encumbered but modestly acidic Lewis acid (LA), (4‐Me‐2,6‐tBu2‐C6H2O)AliBu2 ((BHT)AliBu2), to synergistically promote the frustrated Lewis pair (FLP)‐catalyzed living polymerization of methyl methacrylate (MMA), achieving ultrahigh molecular weight (UHMW) poly(methyl methacrylate) (PMMA) with Mn up to 1927 kg mol−1 and narrow molecular weight distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
2
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 76 publications
0
57
2
4
Order By: Relevance
“…Forreaction conditions, see Table 1, entries 3-5. Lewis pair polymerization (LPP), [33,34] as recently reviewed by Chen, [35] for which also NHO-derived examples exist. [36,37] Hence,atriple role is proposed for Mg(HMDS) 2 .F irstly, activation of the epoxide enables zwitterion formation and efficient propagation.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Forreaction conditions, see Table 1, entries 3-5. Lewis pair polymerization (LPP), [33,34] as recently reviewed by Chen, [35] for which also NHO-derived examples exist. [36,37] Hence,atriple role is proposed for Mg(HMDS) 2 .F irstly, activation of the epoxide enables zwitterion formation and efficient propagation.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Considering the high activity, control and livingness feature of LPP, we envisioned the LPP should enable us to synthesize ultrahigh molecular weight (UHMW) polymer. In 2018, we synthesized a series of strong organophosphorus superbase, imidazolin-2ylidenamino substituted phosphines (IAPs), and employed them to combine with different organoaluminum LAs for polymerization of MMA at room temperature [64]. Among the examined LPs, (BHT) Al i Bu 2 /IAP3 exhibited the best polymerization performance, achieving near quantitative monomer conversion at high polymerization rate for all polymerizations with MMA to IAP3 ratio ranging from 400 to 20,000 and furnishing PMMA with medium to UHMW (M n up to 1,927 kg/mol) and narrow MWD (Ð < 1.10).…”
Section: Al-based Lpsmentioning
confidence: 99%
“…18 However, most studies reported the vinyl-addition polymerization (VAP) of MBL through Michael-type addition across the exocyclic double bond to produce P(MBL)VAP (Scheme 1a, pathway a), which is not fully degradable or recyclable. [18][19][20][21][22][23] The selective ROP of MBL to produce recyclable polyesters is even more challenging compared to the ROP of γBL due to the competing polymerization between the highly reactive exocyclic double bond and the low-strained five membered lactone ring. To the best of our knowledge, the only selective ROP of MBL was exemplified by Chen et al by utilizing La[N(SiMe3)2]3 or yttrium based catalysts.…”
Section: Introductionmentioning
confidence: 99%